A Critical Review of Koranic Intertextuality in the poetry of Mahmud Darwish and Amal Donqol - Ali Salimi; Reza kiani (دراسات في اللغة العربيّة وآدابها)
Koranic intertextuality is one of the most frequently used stylistic devices in Arabic resistance poetry. It has a strong presence in poetic productions because it is able to develop the meaning in the poems. It gives the poems depth and make it an entrance to the nature of man. This feature is something different from supporting and consecrating the words of the poet. Moreover, during the past years, there have been errors in relation to Koranic intertextuality- expressions which are inconsistent with the status of the Koran. This article reviews the Koramic intertextuality in a selected sample of Palestinian and Egyptian resistance potry, that is, in the poetry of Mohmud Darwish and Amal Donqol. The review shows that the two poets sometimes go astray in their use of Koranic references.